Fertilizante organomineral líquido contendo substâncias húmicas em soja cultivada sob estresse hídrico - Prado, Marcelo Ribeiro Vilela (2014)
Humic substances are organic compounds found in sediments, soils, water and waste materials. They have positive effects on the physiology and growth of plants and improve the chemical, physical and biological attributes of the soil. In recent years, many new organic fertilizers, soil conditioners and biostimulators containing these substances have been launched in the market. However, there have been very few scientific studies proving the benefits of agricultural use of these products. The objective of this work was to assess the effects of an organomineral fertilizer enriched with humic substances on soybeans submitted to water stress. Two simultaneous experiments were carried out in a greenhouse, one in soil with medium texture and the other in a sandy soil. The soils were corrected to a suitable fertility level and the soil moisture conditions were 90% of the water retention capacity for plants grown without stress and 30% for those cultivated with stress (considered a very severe stress level). The experimental design was randomized blocks in a 2x5 factorial scheme (two moisture levels and five fertilizer doses: 0, 1, 2, 4 and 8 mL dm-3), for a total of 10 treatments for each soil texture, with eight repetitions. The organomineral fertilizer was applied in the soil 21 days after emergence of the plants, and the moisture regimes were established one week later. The parameters measured were plant height, dry mass of aerial parts and of roots (at flowering and harvest), grain yield and leaf concentrations of macro and micronutrients. The organomineral fertilizer was unable to attenuate the effects of water stress on grain yield in either of the soils: the yield declined by more than 50% in the stressed plants in both soils. There was a positive response to fertilizer doses for the other parameters measured. Under water stress, the most efficient doses were 5.5 and 6.5 mL dm-3 in the soils with medium and sandy textures, respectively. There were lower leaf concentrations of N, P and K in the stressed plants and a higher concentration of S. The humic substances favored the uptake of micronutrients, irrespective of the growing condition.